Iron-Nickel Alloy with Starfish-like Shape and Its Unique Magnetic Properties: Effect of Reaction Volume and Metal Concentration on the Synthesized Alloy - Norhan Nady; Noha Salem; Marwa A. A. Mohamed; Sherif H. Kandil (Nanomaterials, 2021)
Iron-nickel alloy is an example of bimetallic nanostructures magnetic alloy, which receives intensive and significant attention in recent years due to its desirable superior ferromagnetic and mechanical characteristics. In this work, a unique starfish-like shape of an iron-nickel alloy with unique magnetic properties was presented using a simple, effective, high purity, and low-cost chemical reduction. There is no report on the synthesis of such novel shape without complex precursors and/or surfactants that increase production costs and introduce impurities, so far. The synthesis of five magnetic iron-nickel alloys with varying iron to nickel molar ratios (10–50% Fe) was undertaken by simultaneously reducing Fe(II) and Ni(II) solution using hydrazine hydrate as a reducing agent in strong alkaline media for 15 min at 95–98 °C. The effect of reaction volume and total metal concentration on the properties of the synthesized alloys was studied. Alloy morphology, chemical composition, crystal structure, thermal stability, and magnetic properties of synthesized iron-nickel alloys were characterized by means of SEM, TEM, EDX, XRD, DSC and VSM. ImageJ software was used to calculate the size of the synthesized alloys. A deviation from Vegard’s law was recorded for iron molar ration higher than 30%., in which superstructure phase of FeNi3 was formed and the presence of defects in it, as well as the dimensional effects of nanocrystals. The saturation magnetization (Ms), coercivity (Hc), retentivity (Mr), and squareness are strongly affected by the molar ratio of iron and nickel and reaction volume as well as the total metal concentration.